A castable high-performance recyclable polyimide composite material and a preparation method thereof
Patent Information
- Application Number
- CN202610763824.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-29
- Publication Date
- 2026-10-16
AI Technical Summary
高量溶剂体系在加工过程中填料容易沉降与分布不均,导致复合材料难以采用简便成熟的浇注成型工艺;当降低溶剂用量时,聚亚胺预聚物体系又易发生局部瞬时交联,导致体系流动性丧失,无法可控浇注与成型加工
[0024](1)具备优异的可浇注成型能力,应用场景更广泛。本发明提供的可浇注成型的高性能可回收聚亚胺复合材料兼具良好的流动性与快速凝胶行为,能够直接通过浇注方式实现复杂形状制品的成型,无需依赖高压或复杂模压工艺,即可制备获得包括挂件、摆件、棋类制品及积木等在内的多种结构件与日用品,显著提升聚亚胺复合材料在结构功能一体化制品及个性化制造领域的应用潜力,同时更契合工业化连续成型需求。
Smart Images

Figure CN122917534A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer composite materials technology, specifically to a castable, high-performance, recyclable polyimide composite material and its preparation method. Background Technology
[0002] Thermosetting resin composites are widely used in everyday consumer goods due to their excellent mechanical properties, dimensional stability, and heat resistance. However, traditional thermosetting resins typically rely on irreversible covalent cross-linked network structures, making them difficult to remelt or reshape once cured; furthermore, they are difficult to degrade. Therefore, thermosetting resin composites primarily rely on landfill or incineration for disposal after their service life, leading to secondary pollution and resource waste. Polyimide, as a polymer matrix with a dynamic covalent cross-linked network, allows its cross-linked network to undergo topological rearrangement through reversible exchange reactions of imine bonds. Therefore, composites prepared using polyimide as a matrix retain the excellent properties of traditional thermosetting resin composites while also possessing properties such as heat processability, repairability, recyclability, and controllable degradation.
[0003] However, existing polyimide composite materials still face significant limitations in their preparation and processing. Current polyimide composite synthesis systems require solvents. High solvent content in these systems leads to filler sedimentation and uneven distribution during processing, making it difficult to employ simple and mature casting molding processes. Conversely, reducing solvent content causes localized instantaneous cross-linking of the polyimide prepolymer system, resulting in loss of fluidity and hindering controllable casting and molding. Therefore, existing polyimide composite synthesis technologies are incompatible with fillers, primarily using long fibers and textiles as matrices. These matrices must be pre-fixed in molds before the polyimide prepolymer solution is injected and cured (as described in patent CN2024109888801), resulting in complex processes and poor processing flexibility. Therefore, achieving synergistic control between high performance, recyclability, and good processability in polyimide composite materials has become a critical scientific problem and engineering bottleneck that urgently needs to be addressed in this field.
[0004] To address the shortcomings of existing technologies, this invention proposes a novel technical solution. This invention utilizes waste *Morchella alpineensis* mycelium (as described in patent CN2017100343306) from industrial arachidonic acid oil extraction, pre-treated to prepare a micron-sized filler, which is then uniformly mixed with a polyimide prepolymer solution and used to prepare a composite material through a casting process. This mycelium filler has low density and micron-sized dimensions, allowing it to easily suspend in the polyimide prepolymer system. Furthermore, its natural filamentous structure can physically entangle with the polyimide prepolymer molecular chains, effectively inhibiting filler sedimentation. Simultaneously, this filler does not contain active functional groups participating in condensation reactions, and in high-concentration prepolymer systems, it can inhibit rapid local cross-linking to a certain extent, maintaining appropriate fluidity to meet casting requirements. After casting, the polyimide system can still rapidly cross-link to form a gel, further preventing filler sedimentation and uneven distribution. This achievement enables synergistic regulation of polyimide composites in terms of high performance, recyclability, and good processability, providing a new technological path for the high-value utilization of bio-based waste filamentous fungal mycelia and the development of sustainable high-performance composite materials. Summary of the Invention
[0005] To address the shortcomings of the existing technologies, this invention provides a high-performance recyclable polyimide composite material that can be castable and its preparation method, thereby solving the problem that polyimide composite materials are difficult to achieve both high performance and recyclability while being castable.
[0006] To achieve the above objectives, the specific technical solution of the present invention is as follows:
[0007] In a first aspect, the present invention provides a high-performance recyclable polyimide composite material that can be cast, the raw materials of which include: a polyimide prepolymer solution and pretreated filamentous fungal mycelium; wherein, the polyimide prepolymer solution includes aromatic dialdehyde, polyethyleneimine, aromatic diamine and a mixed solvent.
[0008] Further, the mass ratio of the aromatic dialdehyde, polyethyleneimine, aromatic diamine, mixed solvent, and pretreated filamentous fungal mycelium is 1:(2.5-4):(1-2):(5-10):(1-35).
[0009] Furthermore, the pretreatment involves mechanically grinding the mycelium of the filamentous fungi and then screening it through a 100-300 mesh sieve.
[0010] Furthermore, the filamentous fungi include *Morchella alpineensis*.
[0011] Further, the mixed solvent includes a mixture of tetrahydrofuran and ethanol or methanol, wherein the mass ratio of tetrahydrofuran to ethanol / methanol is (20-30):1. For example, the mixed solvent is a mixture of tetrahydrofuran and ethanol with a mass ratio of (20-30):1, or a mixture of tetrahydrofuran and methanol with a mass ratio of (20-30):1.
[0012] Furthermore, the aromatic dialdehyde includes, but is not limited to, at least one of 4,4'-biphenyldialdehyde, terephthalaldehyde, and 4,4''-terphenyldialdehyde.
[0013] Furthermore, the polyethyleneimine includes at least one of polyethyleneimine with a weight-average molecular weight of 300, 600, and 1800.
[0014] Furthermore, the aromatic diamine includes, but is not limited to, at least one of 4,4'-bis(4-aminophenoxy)biphenyl, 2,2'-bis[4-(4-aminophenoxyphenyl)]propane, and 2,2'-bis[4-(4-aminophenoxyphenyl)]propane.
[0015] Secondly, the present invention provides a method for preparing a castable, high-performance, recyclable polyimide composite material, comprising the following steps:
[0016] The polyimide prepolymer solution and the pretreated filamentous fungal mycelium are mixed evenly and poured into a mold. The mixture is then cured under heating conditions to obtain a high-performance recyclable polyimide composite material that can be cast.
[0017] Furthermore, the heating conditions are three-gradient heating; wherein, the first gradient temperature is 20-40 ℃ and the heating time is 3-6 h; the second gradient temperature is 90-120 ℃ and the heating time is 1-3 h; and the third gradient temperature is 150-180 ℃ and the heating time is 1-3 h.
[0018] To address the problem that existing composite materials often fail to simultaneously possess casting properties, recyclability, and reusability, this invention provides a high-performance polyimide composite material that can be cast and molded, exhibits good processability, and is recyclable. This offers a new technological path for the high-value utilization of bio-based waste filamentous fungal mycelia and the development of sustainable high-performance composite materials. The polyimide composite material uses micron-sized *Morchella alpineensis* mycelia as filler. This invention achieves synergistic regulation of the rheological behavior and crosslinking kinetics of the polyimide prepolymer system by strictly controlling the ratio of filler to aromatic dialdehydes, polyethyleneimine, aromatic diamines, and mixed solvents. This is specifically reflected in the following two aspects:
[0019] (1) Sedimentation inhibition and reaction slow-release effect of micron-sized mycelial packing:
[0020] This invention pre-treats the mycelium of filamentous fungi into micron-sized fillers, mixes them uniformly with a polyimide prepolymer solution, and then heats and solidifies them to form a high-performance, recyclable polyimide composite material that can be cast. This mycelium micron-sized filler has low density and micron-sized characteristics, allowing for uniform dispersion in the polyimide prepolymer system. Furthermore, its natural filamentous structure can physically entangle with the prepolymer molecular chains, moderately increasing the system viscosity and effectively inhibiting filler sedimentation. Simultaneously, the mycelium does not contain active functional groups involved in aldehyde-amine condensation reactions. In a high-concentration polyimide prepolymer system, it can, to a certain extent, inhibit / block the diffusion of local reactants and slow down the local reaction rate, thereby suppressing rapid local cross-linking behavior and maintaining suitable fluidity within the processing window, ensuring the controllability of the casting process. After casting, under heating conditions, the polyimide system can still rapidly cross-link and form a gel, further preventing filler migration and structural inhomogeneity.
[0021] (2) Synergistic regulatory effect of reaction system components on crosslinking behavior and processing window:
[0022] In the reaction system, polyethyleneimine, with its long-chain structure, enhances the entanglement between molecular chains and between the system and the filler, thereby inhibiting filler migration and sedimentation. Simultaneously, as a crosslinking agent, it exhibits high amino reactivity, promoting rapid crosslinking and gel solidification after casting, further suppressing filler sedimentation. On the other hand, the nucleophilicity of the amino groups in the aromatic diamines is significantly lower than that of aliphatic diamines due to the electron-withdrawing effect of the benzene ring; especially aromatic diamines containing multiple benzene rings, whose reactivity is further reduced due to conjugation effects, enhanced electron delocalization, increased molecular rigidity, and increased steric hindrance. This invention utilizes aromatic diamines containing multiple benzene rings to further reduce the overall reaction rate in high-concentration systems, avoiding localized instantaneous crosslinking caused by excessively rapid reactions, thus preventing a sudden drop in system fluidity and structural inhomogeneity, and ensuring a suitable casting processing window.
[0023] Compared with the prior art, the advantages of the present invention are:
[0024] (1) It has excellent casting molding capability and a wider range of application scenarios. The high-performance recyclable polyimide composite material that can be cast in this invention has both good flowability and rapid gelation behavior. It can directly achieve the molding of complex-shaped products by casting without relying on high pressure or complex molding processes. It can prepare a variety of structural parts and daily necessities, including pendants, ornaments, chess products and building blocks, which significantly enhances the application potential of polyimide composite materials in the fields of integrated structural and functional products and personalized manufacturing, while also better meeting the needs of industrial continuous molding.
[0025] (2) Significantly reduces solvent consumption, balancing cost and environmental advantages. By constructing a high-concentration prepolymer system, this invention reduces solvent consumption by approximately 30%-80% compared to existing technologies, effectively reducing the use and emissions of organic solvents. On the one hand, it significantly reduces raw material and post-processing costs; on the other hand, it reduces volatile organic compound emissions, improving the green environmental friendliness and safety of the process, and better meeting the requirements of current green manufacturing and sustainable development.
[0026] (3) Adaptable to fillers and achieves ultra-high filler loading, breaking through the bottleneck of existing systems. The polyimide prepolymer system of the present invention can be mixed with fillers, breaking through the bottleneck that the existing polyimide system can only be adapted to matrices such as textiles and yarns, and cannot be adapted to fillers. In addition, the filler content in the composite material is increased to 70%-90% (wt%), which is significantly higher than the level of filler usage in existing composite materials (≤ 60%). The high filler content system of the present invention reduces the amount of polymer matrix used, further reducing material costs, and provides an effective way for the high-value utilization of low-cost filler resources such as filamentous fungal mycelium waste.
[0027] (4) Possesses excellent mechanical properties, heat resistance, and recyclability. The castable high-performance recyclable polyimide composite material of this invention still exhibits excellent comprehensive performance under high filler content conditions. In terms of mechanical properties, the castable high-performance recyclable polyimide composite material has good load-bearing capacity, and the box made of the polyimide composite material can withstand pressure exceeding 10,000 times its own weight; in terms of heat resistance, the glass transition temperature of the castable high-performance recyclable polyimide composite material is higher than 160 ℃, which can meet the requirements of medium and high temperature use; in terms of recycling, based on the dynamic covalent network structure of polyimide, the castable high-performance recyclable polyimide composite material can achieve closed-loop recycling and reprocessing, and the performance of the recycled material does not significantly degrade. Attached Figure Description
[0028] Figure 1 The Tan δ curve as a function of temperature for the castable high-performance recyclable polyimide composite material in Example 1;
[0029] Figure 2 This is a cross-sectional scanning electron microscope image of the high-performance recyclable polyimide composite material that can be cast in Example 1.
[0030] Figure 3 The pressure versus displacement curve of the castable high-performance recyclable polyimide composite material in Example 1 is shown.
[0031] Figure 4 This refers to the polyimide composite material molded product prepared using a butterfly pendant mold in Example 1;
[0032] Figure 5 The curve of Tan δ versus temperature for the castable high-performance recyclable polyimide composite material in Example 2;
[0033] Figure 6 This is a cross-sectional scanning electron microscope image of the high-performance recyclable polyimide composite material that can be cast in Example 2;
[0034] Figure 7 The pressure versus displacement curve of the castable high-performance recyclable polyimide composite material in Example 2;
[0035] Figure 8 Example 2 shows a polyimide composite molded product prepared using a heart-shaped ornament mold;
[0036] Figure 9 The curve of Tan δ as a function of temperature for the castable high-performance recyclable polyimide composite material in Example 3;
[0037] Figure 10 This is a cross-sectional scanning electron microscope image of the high-performance recyclable polyimide composite material that can be cast in Example 3;
[0038] Figure 11 The pressure versus displacement curve of the castable high-performance recyclable polyimide composite material in Example 3;
[0039] Figure 12 Example 3 shows a polyimide composite material molded product prepared using a chess mold;
[0040] Figure 13 The Tan δ curve as a function of temperature is shown for the high-performance recyclable polyimide composite material that can be cast and molded after depolymerization in Example 4.
[0041] Figure 14 Cross-sectional scanning electron microscope image of the high-performance recyclable polyimide composite material that was re-prepared after depolymerization in Example 4;
[0042] Figure 15 Example 4: Pressure versus displacement curve of a castable, high-performance, recyclable polyimide composite material reconstituted after depolymerization;
[0043] Figure 16 Example 4 shows a molded product made from recycled polyimide composite material prepared using a building block toy mold;
[0044] Figure 17 The polyimide prepolymer in Comparative Example 1, after being stirred evenly, cannot be cast into shape.
[0045] Figure 18 The curve of Tan δ as a function of temperature for the polyimide material in Comparative Example 1 is shown.
[0046] Figure 19 The pressure versus displacement curve of the polyimide material in Comparative Example 1 is shown.
[0047] Figure 20 The polyimide composite prepolymer in Comparative Example 2, after being stirred evenly, cannot be cast into shape.
[0048] Figure 21 The curve of Tan δ as a function of temperature for the polyimide composite material in Comparative Example 2 is shown.
[0049] Figure 22 This is a scanning electron microscope image of a cross section of the polyimide composite material in Comparative Example 2;
[0050] Figure 23 The pressure versus displacement curve of the polyimide composite material in Comparative Example 2 is shown.
[0051] Figure 24 The polyimide composite prepolymer in Comparative Example 3, after being stirred evenly, could not be cast into shape.
[0052] Figure 25 The curve of Tan δ as a function of temperature for the polyimide composite material in Comparative Example 3;
[0053] Figure 26 This is a scanning electron microscope image of a cross section of the polyimide composite material in Comparative Example 3;
[0054] Figure 27 The pressure versus displacement curve of the polyimide composite material in Comparative Example 3 is shown.
[0055] Figure 28 The polyimide composite prepolymer in Comparative Example 4, after being stirred evenly, could not be cast into shape.
[0056] Figure 29 The curve of Tan δ as a function of temperature for the polyimide composite material in Comparative Example 4;
[0057] Figure 30 This is a scanning electron microscope image of a cross section of the polyimide composite material in Comparative Example 4.
[0058] Figure 31 The pressure-displacement curve of the polyimide composite material in Comparative Example 4 is shown. Detailed Implementation
[0059] To enable those skilled in the art to clearly and completely understand the technical solution of the present invention, the present invention will be further described in detail below with reference to embodiments. Obviously, the embodiments described herein are only for explaining the present invention and are not intended to limit the scope of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0060] Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in this invention are conventional reagents, methods and equipment in the art.
[0061] This invention provides a high-performance recyclable polyimide composite material that can be cast, the raw materials of which include: a polyimide prepolymer solution and pretreated filamentous fungal mycelium; wherein, the polyimide prepolymer solution includes aromatic dialdehyde, polyethyleneimine, aromatic diamine and mixed solvent; the pretreatment is performed by mechanically grinding the filamentous fungal mycelium.
[0062] In some examples, the mass ratio of the aromatic dialdehyde, polyethyleneimine, aromatic diamine, mixed solvent, and pretreated filamentous fungal mycelium is 1:(2.5-4):(1-2):(5-10):(1-35).
[0063] In some examples, the mixed solvent comprises a mixture of tetrahydrofuran and ethanol or methanol in a mass ratio of (20-30):1; the aromatic dialdehyde includes, but is not limited to, at least one of 4,4'-biphenyldicarboxaldehyde, terephthalaldehyde, and 4,4''-terphenyldicarboxaldehyde; the polyethyleneimine includes, but is not limited to, at least one of polyethyleneimine with a weight-average molecular weight of 300, 600, and 1800; the aromatic diamine includes, but is not limited to, at least one of 4,4'-bis(4-aminophenoxy)biphenyl, 2,2'-bis[4-(4-aminophenoxyphenyl)]propane, and 2,2'-bis[4-(4-aminophenoxyphenyl)]propane.
[0064] The method for preparing the castable, high-performance, recyclable polyimide composite material includes the following steps:
[0065] The polyimide prepolymer solution and the pretreated filamentous fungal mycelium are mixed evenly and poured into a mold. The mixture is then cured under heating conditions to obtain a high-performance recyclable polyimide composite material that can be cast.
[0066] In some examples, the heating conditions are three-gradient heating; wherein the first gradient temperature is 20-40 ℃ and the heating time is 3-6 h; the second gradient temperature is 90-120 ℃ and the heating time is 1-3 h; and the third gradient temperature is 150-180 ℃ and the heating time is 1-3 h.
[0067] In the following specific embodiments, the *Mortierella alpina* is *Mortierella alpina* M0223, provided by the Institute of Resource Biology and Biotechnology, School of Life Science and Technology, Huazhong University of Science and Technology. *Mortierella alpina* M0223 was deposited on March 10, 2003, at the China General Microbiological Culture Collection Center (CGMCC), accession number CGMCC NO.0903, located at No. 13, Zhongguancun North First Street, Haidian District, Beijing, Institute of Microbiology, Chinese Academy of Sciences, Postcode: 100080 (see patent CN2003101112966).
[0068] Example 1
[0069] This embodiment provides a castable, high-performance, recyclable polyimide composite material. The raw materials for the polyimide composite material are: aromatic dialdehyde, polyethyleneimine, aromatic diamine, mixed solvent, and filler in a mass ratio of 1:2.5:2:10:1; wherein the aromatic dialdehyde is 4,4'-biphenyldicarboxaldehyde; the polyethyleneimine has a weight-average molecular weight of 300; the aromatic diamine is 4,4'-bis(4-aminophenoxy)biphenyl; the mixed solvent is a mixture of tetrahydrofuran and ethanol in a mass ratio of 20:1; and the filler is obtained by mechanically grinding the mycelium of *Morchella alpina* followed by sieving through a 100-mesh sieve.
[0070] The preparation method of the castable high-performance recyclable polyimide composite material is as follows:
[0071] Aromatic diamines were dissolved in a mixed solvent, followed by the addition of polyethyleneimine. After stirring until homogeneous, aromatic dialdehyde (30 g) was added, and finally filler was added. After stirring until homogeneous, the mixture was poured into a square mold (length x width x height: 250 × 250 × 5 mm) or a butterfly pendant mold. The mixture was then treated at 20 ℃ for 3 h, at 120 ℃ for 2 h, and at 150 ℃ for 3 h to obtain a high-performance recyclable polyimide composite material that can be cast.
[0072] High-performance, recyclable polyimide composite material prepared using a square mold was cut into 15 mm × 5 mm pieces, and its glass transition temperature was determined using a dynamic thermal analyzer. Figure 1 As shown, the glass transition temperature of the castable, high-performance, recyclable polyimide composite material reaches 165 °C. Figure 2 As shown, scanning electron microscopy analysis of the cross-section of the castable, high-performance, recyclable polyimide composite material revealed that the filler was uniformly dispersed within the polyimide matrix. Figure 3 As shown, a high-performance, recyclable polyimide composite material prepared using a square mold was cut into four 100 mm × 50 mm × 5 mm sheets and riveted together to form a box (approximately 91 g). This box could withstand a pressure of approximately 9 kN, exceeding its own weight by about 10,000 times. When the mold used was a butterfly pendant mold, the resulting molded polyimide composite material product was as follows... Figure 4 As shown.
[0073] Example 2
[0074] This embodiment provides a castable, high-performance, recyclable polyimide composite material and its molded product. The raw materials for the polyimide composite material are: aromatic dialdehyde, polyethyleneimine, aromatic diamine, mixed solvent, and filler in a mass ratio of 1:3:1.5:7:15; wherein the aromatic dialdehyde is 4,4''-terphenyldialdehyde; the polyethyleneimine has a weight-average molecular weight of 600; the aromatic diamine is 2,2'-bis[4-(4-aminophenoxyphenyl)]propane; the mixed solvent is a mixture of tetrahydrofuran and methanol in a mass ratio of 25:1; and the filler is obtained by mechanically grinding the mycelium of *Morchella alpina* followed by sieving through a 200-mesh sieve.
[0075] The preparation method of the castable high-performance recyclable polyimide composite material is as follows:
[0076] Aromatic diamines were dissolved in a mixed solvent, followed by the addition of polyethyleneimine. After stirring until homogeneous, aromatic dialdehyde (30 g) was added, and finally filler was added. After stirring until homogeneous, the mixture was poured into a square mold (length x width x height: 250 × 250 × 5 mm) or a heart-shaped ornament mold. The mixture was then treated at 30 ℃ for 4 h, at 100 ℃ for 1 h, and at 160 ℃ for 2 h to obtain a high-performance recyclable polyimide composite material that can be cast.
[0077] like Figure 5 As shown, the glass transition temperature of the castable, high-performance, recyclable polyimide composite material reaches 183 °C. Figure 6 As shown, scanning electron microscopy analysis of the cross-section of the castable, high-performance, recyclable polyimide composite material revealed that the filler was uniformly dispersed within the polyimide matrix. Figure 7As shown, a high-performance, recyclable polyimide composite material prepared using a square mold was cut into four 100 mm × 50 mm × 5 mm sheets and riveted together to form a box (96 g). This box could withstand a pressure of approximately 9 kN, exceeding its own weight by about 10,000 times. When a heart-shaped ornament mold was used, the resulting molded polyimide composite material product was as follows. Figure 8 As shown.
[0078] Example 3
[0079] This embodiment provides a castable, high-performance, recyclable polyimide composite material and its molded product. The raw materials for the polyimide composite material are: aromatic dialdehyde, polyethyleneimine, aromatic diamine, mixed solvent, and filler in a mass ratio of 1:4:1:5:35; wherein the aromatic dialdehyde is terephthalaldehyde; the polyethyleneimine has a weight-average molecular weight of 1800; the aromatic diamine is 2,2'-bis[4-(4-aminophenoxyphenyl)]propane; the mixed solvent is a mixture of tetrahydrofuran and ethanol in a mass ratio of 30:1; and the filler is obtained by mechanically grinding the mycelium of *Morchella alpina* followed by sieving through a 300-mesh sieve.
[0080] The preparation method of the castable high-performance recyclable polyimide composite material is as follows:
[0081] Aromatic diamines were dissolved in a mixed solvent, followed by the addition of polyethyleneimine. After stirring until homogeneous, aromatic dialdehyde (30 g) was added, and finally filler was added. After stirring until homogeneous, the mixture was poured into a square mold (length x width x height: 250 × 250 × 5 mm) or a chess mold. The mixture was then treated at 40 ℃ for 1 h, at 90 ℃ for 3 h, and at 180 ℃ for 1 h to obtain a high-performance recyclable polyimide composite material that can be cast.
[0082] High-performance, recyclable polyimide composite material prepared using a square mold was cut into 15 mm × 5 mm pieces, and its glass transition temperature was determined using a dynamic thermal analyzer. Figure 9 As shown, the glass transition temperature of the castable, high-performance, recyclable polyimide composite material reaches 186 °C. Figure 10 As shown, scanning electron microscopy analysis of the cross-section of the castable, high-performance, recyclable polyimide composite material revealed that the filler was uniformly dispersed within the polyimide matrix. Figure 11As shown, a high-performance, recyclable polyimide composite material prepared using a square mold was cut into four 100 mm × 50 mm × 5 mm sheets and riveted together to form a box (100 g). This box could withstand a pressure of approximately 9 kN, exceeding its own weight by about 10,000 times. When a chess mold was used, the resulting molded polyimide composite material product was as follows... Figure 12 As shown.
[0083] Example 4
[0084] The high-performance recyclable polyimide composite material that can be cast in Example 3 was immersed in a mixed solvent (tetrahydrofuran and ethanol) containing polyethyleneimine, wherein the amount of polyethyleneimine and the mixed solution was the same as that used in the preparation of the high-performance recyclable polyimide composite material in Example 3; then, it was stirred at a rate of 50 rpm for 1 h, and the high-performance recyclable polyimide composite material that can be cast in Example 3 was depolymerized; after depolymerization, aromatic dialdehyde, aromatic diamine and filler were added to the mixed system according to the reaction system of Example 3, and after stirring evenly, the high-performance recyclable polyimide composite material that can be cast in Example 3 was prepared again.
[0085] High-performance, recyclable polyimide composite material prepared using a square mold was cut into 15 mm × 5 mm pieces, and its glass transition temperature was determined using a dynamic thermal analyzer. Figure 13 As shown, the glass transition temperature of the castable, high-performance, recyclable polyimide composite material reaches 184 °C. Figure 14 As shown, scanning electron microscopy analysis of the cross-section of the castable, high-performance, recyclable polyimide composite material revealed that the filler was uniformly dispersed within the polyimide matrix in the reconstituted composite. Figure 15 As shown, the reconstituted composite material was cut into four 100 mm × 50 mm × 5 mm sheets and riveted together to form a box (99 g). This box could withstand a pressure of approximately 9 kN, exceeding its own weight by about 10,000 times. When a building block mold was used to reconstitute the composite material, the resulting molded product was as follows. Figure 16 As shown.
[0086] Comparative Example 1
[0087] The polyimide material in this comparative example is prepared in essentially the same way as in Example 3, except that no filler is added. This comparative example is prepared by uniformly mixing aromatic diamine, mixed solvent, polyethyleneimine, and aromatic dialdehyde in the order described in Example 3. Figure 17 As shown, it cannot be formed by casting.
[0088] In this comparative example, the obtained mixture was coated into a square mold (length × width × height: 250 × 250 × 5 mm) and then cured using the heating method described in Example 3 to obtain a polyimide material. The polyimide material was cut into 15 mm × 5 mm pieces, and the glass transition temperature of this comparative example polyimide material was measured using a dynamic thermal analyzer to be only about 152 °C (see Example 3). Figure 18 The polyimide material was cut into four 100 mm × 50 mm × 5 mm sheets and riveted together to form a box (90 g). This box could only withstand a pressure of about 0.7 kN, which is about 760 times its own weight (see...). Figure 19 ).
[0089] Comparative Example 2
[0090] The polyimide composite material in this comparative example is prepared in essentially the same way as in Example 3, except that this comparative example uses yeast that has undergone the same pretreatment as the filler. In this comparative example, aromatic diamine, mixed solvent, polyethyleneimine, aromatic dialdehyde, and filler are mixed evenly in the order of Example 3 to form a mixture, as shown below. Figure 20 As shown, it cannot be formed by casting.
[0091] In this comparative example, the obtained mixture was coated into a square mold (length × width × height: 250 × 250 × 5 mm) and then cured using the heating method described in Example 3 to obtain a polyimide composite material. The polyimide composite material was cut into 15 mm × 5 mm pieces, and the glass transition temperature of this comparative example polyimide composite material was measured using a dynamic thermal analyzer to be only about 127 °C (see Example 3). Figure 21 ); Scanning electron microscopy analysis of the cross-section of the polyimide composite material revealed obvious delamination between the filler and the matrix (see...). Figure 22 The polyimide composite material was cut into four 100 mm × 50 mm × 5 mm sheets and riveted together to form a box (92 g). This box could only withstand a pressure of about 0.45 kN, which is about 500 times its own weight (see...). Figure 23 ).
[0092] Comparative Example 3
[0093] The polyimide composite material in this comparative example is prepared in basically the same way as in Example 3, except that the mass ratio of terephthalaldehyde to polyethyleneimine is reduced to 1:2. This comparative example is a mixture formed by uniformly mixing aromatic diamine, mixed solvent, polyethyleneimine, aromatic dialdehyde, and filler in the order of Example 3. Figure 24 As shown, it cannot be formed by casting.
[0094] In this comparative example, the obtained mixture was coated into a square mold (length × width × height: 250 × 250 × 5 mm) and then cured using the heating method described in Example 3 to obtain a polyimide composite material. The polyimide composite material was cut into 15 mm × 5 mm pieces, and the glass transition temperature of this comparative example polyimide composite material was measured using a dynamic thermal analyzer to be only about 87 °C (see Example 3). Figure 25 ); Scanning electron microscopy analysis of the cross-section of the polyimide composite material revealed obvious delamination between the filler and the matrix (see...). Figure 26 The polyimide composite material was cut into four 100 mm × 50 mm × 5 mm sheets and riveted together to form a box (102 g). This box could only withstand a pressure of about 0.1 kN, which is about 100 times its own weight (see...). Figure 27 ).
[0095] Comparative Example 4
[0096] The polyimide composite material in this comparative example is prepared in essentially the same way as in Example 3, except that tetramethyl-p-phenylenediamine is used in an equimolar ratio instead of 2,2'-bis[4-(4-aminophenoxyphenyl)]propane. In this comparative example, the aromatic diamine, mixed solvent, polyethyleneimine, aromatic dialdehyde, and filler are mixed uniformly in the order described in Example 3 to form a mixture, such as... Figure 28 As shown, it cannot be formed by casting.
[0097] In this comparative example, the obtained mixture was coated into a square mold (length x width x height: 250 × 250 × 5 mm) and then cured using the heating method described in Example 3 to obtain a polyimide composite material. The polyimide composite material was cut into 15 mm × 5 mm pieces, and the glass transition temperature of this comparative example polyimide composite material was measured using a dynamic thermal analyzer to be only about 135 °C (see Example 3). Figure 29 ); Scanning electron microscopy analysis of the cross-section of the polyimide composite material revealed obvious delamination between the filler and the matrix (see...). Figure 30 The polyimide composite material was cut into four 100 mm × 50 mm × 5 mm sheets and riveted together to form a box (92 g). This box could only withstand a pressure of about 0.55 kN, which is about 600 times its own weight (see...). Figure 31 ).
[0098] As can be seen from the above examples and comparative experimental results, the present invention, by using *Morchella alpineensis* mycelium as a filler and combining it with the optimization of the polyimide synthesis system, enables the direct fabrication of polyimide composite materials into molded products, such as pendants, ornaments, chess sets, and other daily necessities, through a casting molding process. These products also possess excellent heat resistance, compressive strength, and recyclability. In contrast, without the introduction of *Morchella alpineensis* mycelium or by using non-filamentous fungal mycelium as a filler, the composite system cannot simultaneously meet the requirements of casting processability and performance stability, making it difficult to achieve the aforementioned comprehensive effect.
[0099] Furthermore, the experimental results also show that the composition of the composite system has a significant impact on the performance of the final composite material. When the amount of polyethyleneimine is reduced, the degree of cross-linking of the system decreases, the gel curing ability weakens, resulting in a decrease in the mechanical properties and heat resistance of the final composite material. At the same time, the sedimentation of fillers during processing is aggravated. When the number of benzene rings in the aromatic diamine used is reduced, its reactivity increases, which easily triggers local rapid cross-linking of the system, thereby shortening the processing window, leading to decreased fluidity and structural inhomogeneity, and thus affecting the molding quality and overall performance of the final composite material.
[0100] Furthermore, compared with existing polyimide synthesis systems, the polyimide composite material system provided by this invention can significantly reduce the amount of solvent used and greatly shorten the settling time while ensuring the performance of the composite material (see Table 1), effectively improving the preparation efficiency and process feasibility.
[0101] Table 1: Solvent types, volumes, and settling times used in current polyimide synthesis systems
[0102]
[0103] Note: All the above systems are normalized to 15 mmol terephthalaldehyde.
[0104] References:
[0105] 1. Schoustra SK et al. European Polymer Journal, 2023, 195:112209.
[0106] 2. Zhu C. et al. Rsc Advances, 2017, 7(76): 48303-48307.
[0107] 3. Wang S. et al. Macromolecules, 2020, 53(8): 2919-2931.
[0108] 4. Taynton P. et al. Polymer Chemistry, 2016, 7(46): 7052-7056.
[0109] 5. Ding H. et la. Chemical Engineering Journal, 2024, 481: 148024.
[0110] 6. Li, Jiaxin. Preparation and properties of vitrimer based on terephthalaldehyde and dynamic imine bonds. Dalian University of Technology, 2020.
[0111] In summary, this invention uses filamentous fungal mycelium as a filler and, by controlling the composition and ratio of the reaction system, achieves an optimized balance between the casting processability, structural uniformity, and overall performance of polyimide composite materials, thus broadening their application prospects in everyday consumer goods and building decoration.
[0112] The above detailed embodiments describe the implementation of the present invention; however, the present invention is not limited to the specific details described in the above embodiments. Within the scope of the claims and technical concept of the present invention, various simple modifications and changes can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.
Claims
1. A castable, high-performance, recyclable polyimide composite material, characterized in that, Raw materials include: The polyimide prepolymer solution and pretreated filamentous fungal mycelium; wherein the polyimide prepolymer solution comprises aromatic dialdehyde, polyethyleneimine, aromatic diamine and a mixed solvent.
2. The high-performance recyclable polyimide composite material that can be castable according to claim 1, characterized in that, The mass ratio of the aromatic dialdehyde, polyethyleneimine, aromatic diamine, mixed solvent, and pretreated filamentous fungal mycelium is 1:(2.5-4):(1-2):(5-10):(1-35).
3. The high-performance recyclable polyimide composite material that can be castable according to claim 1, characterized in that, The pretreatment involves mechanically grinding the mycelium of filamentous fungi and then screening it through a 100-300 mesh sieve.
4. The high-performance recyclable polyimide composite material that can be castable according to claim 3, characterized in that, The filamentous fungi include Alpine Fibrosum.
5. The high-performance recyclable polyimide composite material that can be castable according to claim 1, characterized in that, The mixed solvent includes a mixture of tetrahydrofuran and ethanol or methanol.
6. The high-performance recyclable polyimide composite material that can be castable according to claim 1, characterized in that, The aromatic dialdehydes include, but are not limited to, at least one of 4,4'-biphenyldialdehyde, terephthalaldehyde, and 4,4''-terphenyldialdehyde.
7. The high-performance recyclable polyimide composite material that can be castable according to claim 1, characterized in that, The polyethyleneimine includes at least one of polyethyleneimine with a weight-average molecular weight of 300, 600, and 1800.
8. The high-performance recyclable polyimide composite material that can be castable according to claim 1, characterized in that, The aromatic diamine includes, but is not limited to, at least one of 4,4'-bis(4-aminophenoxy)biphenyl, 2,2'-bis[4-(4-aminophenoxyphenyl)]propane, and 2,2'-bis[4-(4-aminophenoxyphenyl)]propane.
9. The method for preparing the castable, high-performance, recyclable polyimide composite material according to any one of claims 1-8, characterized in that, Includes the following steps: The polyimide prepolymer solution and the pretreated filamentous fungal mycelium are mixed evenly and poured into a mold. The mixture is then cured under heating conditions to obtain a high-performance recyclable polyimide composite material that can be cast.
10. The method for preparing the castable, high-performance, recyclable polyimide composite material according to claim 9, characterized in that, The heating conditions are three-gradient heating; wherein, the first gradient temperature is 20-40 ℃ and the heating time is 3-6 h; the second gradient temperature is 90-120 ℃ and the heating time is 1-3 h; and the third gradient temperature is 150-180 ℃ and the heating time is 1-3 h.